Laboratory tests of deep composite wood-concrete beam and deck specimens - Gutkowski, Richard Matthew (Proceedings, Annual Conference - Canadian Society for Civil Engineering, 2020)
Experimental and analytical studies of composite wood-concrete floor/deck systems have been ongoing at Colorado State University. An innovative novel shear key/anchor detail for overlaying solid wood floors in office buildings with a concrete layer, thus creating a composite floor, was adapted for this study. The connection detail transfers bearing stress between and shear stress in the joined materials for interlayer force transfer. Prior work was on a geometry intended for floors of moderately loaded systems (residences, offices etc.). In continuation work tests are being conducted on deeper layered beam specimens, intended for heavier loads (warehouses, bridges etc.). Laboratory studies include pull-out tests on the anchors; interlayer slip tests on connection details; and pilot service, repeated load and creep tests of several layered beam specimens. These will be followed by load tests of a full size deep floor/ deck specimen. This paper reports on the outcome of early ramp tests of several specimens.